A COMPARISON OF MYCOPHENOLATE MOFETIL AND CYCLOPHOSPHAMIDE AS LUPUS NEPHRITIS INDUCTION THERAPY - Gul, Haris; Mushtaq, Muhammad Salman; Salim, Babur; Samreen, Saba; Nasim, Amjad; Khan, Muhammad (Journal of Ayub Medical College Abbottabad, 2020)
Background: Lupus nephritis and its induction therapies are under studied subject in rheumatology especially in our population. The objective of this study is to compare the renal response to Mycophenolate mofetil (MMF) and Cyclophosphamide (CYC) as induction therapy in Pakistani population with lupus nephritis. Methods: This is a comparative retrospective study conducted at the department of rheumatology, Fauji Foundation Hospital (FFH), Rawalpindi and duration of study was 1.5 years from July 2016 to December 2017. The study includes 28 patients, all females, ages between 18 to 50 years. All have biopsy proven lupus nephritis (LN). All 28 LN patients have either stage III, IV, V. They were investigated and analysed over a period of 1.5 years. 14 patients were given MMF (2.5 gram/day) (MMF group) and 14 patients were given CYC (NIH protocol/monthly) (CYC group) for 24 weeks as induction therapy. Comparison of baseline characteristics, complete and partial renal responses to treatment was seen in the MMF and CYC groups. Results: Primary end point (complete response) is achieved in 6 (42.85%) in MMF group and 5 (35.71%) in the CYC group. Secondary end point (partial response) was achieved in 5 (35.71%) patients in the MMF group and 6(42.85%) in the CYC group. Difference in cumulative probability of complete and partial response was not statistically significant between the two groups (P-0.470 for CR) and (p-value 0.132 for PR). Conclusion: Mycophenolate mofetil is a new therapy for LN and it has equal efficacy as compared to CYC for LN induction. Keywords: Lupus nephritis; Induction therapy; Mycophenolate Mofetil; Cyclophosphamide